Treatment of toe walking in patients with autism spectrum disorder: An integrative literature review (Research, Society and Development, 2024)
Autism Spectrum Disorder (ASD) is a complex condition that presents the following characteristics: deficits in communication, social interaction, and restricted and repetitive behavioral patterns. In addition to manifestations related to neurodevelopment and social interaction, many individuals also present atypical motor manifestations, such as variations in gait and posture, including the phenomenon of toe walking (TW), which can exacerbate the adaptive dysfunction present in this group. and compromise quality of life. The present study is configured as an integrative literature review. Data collection was carried out between September and October 2023. The objective of the article was to find the best management of tiptoe walking in patients with ASD. The work proposes that early identification and intervention are of paramount importance to optimize clinical outcomes. The management of toe walking encompasses a range of interventions ranging from conservative approaches to surgical procedures, with age being a determinant of therapeutic efficacy. The absence of standardized guidelines highlights the need for additional research and in-depth discussions to establish an effective and uniform treatment protocol.